Computer simulation studies of carbon nanotube and its interactions with water - Vijayaraghavan Venkatesh (2014)
Recent discoveries of various forms of nano-materials have stimulated research on their applications in diverse fields. Of particular mention is the carbon nanotubes (CNTs) whose unique mechanical and physical properties has triggered a wide-spread research interest in a broad range of innovative application in a number of fields such as nanoelectronics, nano-fluidics, biosensors, marine, biological and medical applications. Design of CNT based nano-drug delivery devices have also been a rapidly emerging research in the field of nano-biotechnology. Most of these applications involve interaction of CNTs with water and water based solutions. Much of the underlying physical phenomena such as the effect of water interaction dynamics on the mechanical properties of CNTs remains to be investigated. A thorough knowledge on the influence of water molecule interactions on the mechanical and transport properties of CNTs is useful to determine the lifetime and stability of CNT based nano-fluidics and NEMS devices. In view of this, the major focus of this thesis is to study and understand the mechanical properties of CNTs interacting with water molecules by employing molecular dynamics (MD) simulation. The mechanical properties of single-walled CNTs (SWCNTs) interacting with water molecules have been studied by subjecting the SWCNT to four forms of mechanical loading conditions – compression, tension, torsion and shear. The results indicate that the mechanical performance of SWCNT is strongly affected due to interaction of the surrounding water molecules. In addition, the influence of the SWCNT geometry on the mechanical properties of water submerged SWCNTs is examined. The MD simulations show that SWCNTs with large diameter performs better than SWCNTs with small diameter under mechanical loading. The results also demonstrate that in addition to defect concentration, the location of defects in SWCNT will also affect the mechanical properties of water submerged SWCNT. For the case of capped SWCNTs, it was found that the concentration of water molecule encapsulated inside the SWCNT strongly affects the elastic properties of the SWCNT. Another study involved the transport characteristics of water molecules in CNTs using MD simulation. The transport properties of water molecules in a nano-scale channel such as CNTs is critical for its key role in designing the next generation CNT based nanofluidic devices. The effect of channel diameter, defects and the inter-layer spacing on the transport of water molecules is studied by subjecting the flow of water molecules through CNTs under pressure. The findings show that the efficiency of water transport can be improved by deploying bigger SWCNTs that have wide channel diameter. It was however found that defects in the nano-fluidic system will reduce the transport efficiency of water molecules. The results also show that the inter-layer spacing in a double-walled CNTs (DWCNTs) has a significant influence on the transport efficiency of water molecules. The investigations and conclusions obtained from this thesis is expected to further compliment the potential applications of CNTs in nano-fluidics and NEMS devices.